Wywiad [przełożył Tomasz Kaczmarek] - Mirbeau, Octave (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
Translation of a one-act comedy Interview is the second work by Octave Mirbeau published in Poland. Mirbeau (1848-1917) was a French free-thinker and anarchist, exponent of “theater of combat”, whose message – popular in the era of the Third Republic – was adopted by emancipatory movements of the 1960s and 1970s. The play premiered on February 2, 1909 in Grand-Guignol. This translation was made from the original edition: Octave Mirbeau, Théâtre complet. Textes choisis, établis et presentes par Pierre Michel, Eurédit, 2003 pp. 195–215. All comments are by the translator .